2007
DOI: 10.1016/j.jvs.2006.11.057
|View full text |Cite
|
Sign up to set email alerts
|

Depression is associated with worse patency and recurrent leg symptoms after lower extremity revascularization

Abstract: Depression is common among patients undergoing intervention for symptomatic PAD. After intervention, patients with depression have worse outcomes for the affected leg. Prospective analysis is required to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 31 publications
2
49
0
4
Order By: Relevance
“…In a separate manuscript, we reported that patients with depression at the time of PAD intervention were at increased risk for failure of the revascularization and recurrent symptoms in the treated leg. 5 To our knowledge, the present study is the first to examine the association between depression at the time of PAD intervention and mortality or subsequent cardiovascular events in other vascular beds.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In a separate manuscript, we reported that patients with depression at the time of PAD intervention were at increased risk for failure of the revascularization and recurrent symptoms in the treated leg. 5 To our knowledge, the present study is the first to examine the association between depression at the time of PAD intervention and mortality or subsequent cardiovascular events in other vascular beds.…”
Section: Discussionmentioning
confidence: 90%
“…[5][6][7] For patients with acute coronary syndromes, depression is a risk factor for recurrent cardiovascular events and mortality. [8][9][10] After coronary artery bypass surgery, it is associated with increased risk for recurrent cardiovascular events, 4,11 rehospitalization for cardiac events, 12 repeat coronary revascularization, 4 and death.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depressive symptoms are high among patients with PAD. The presence of depression may be a helpful factor in assessing pain scales in patients with PAD 21-23. However, in our study, patients’ psychological conditions were not considered.…”
Section: Discussionmentioning
confidence: 92%
“…For instance, depression at baseline was associated with worse patency of the revascularization and greater risk for return to symptomatic disease in elderly patients operated for peripheral arterial disease [19]. A recent systematic review [20] found that white matter hyperintensities (WMHs) are more common and more severe among individuals with late-life depression than in healthy controls.…”
Section: Introductionmentioning
confidence: 99%